Alignment of energy transition and water resources under the carbon neutrality target in China - Chenmin He; Kejun Jiang; Pianpian Xiang; Weiyi Jiang; Yifei Zhang (Journal of Integrative Environmental Sciences)
Significant energy transition would be needed in China under the carbon neutrality target. Since it would have important impacts on water resource through increased usage, understanding the water demand under specific climate change targets could enable better policy-making for the energy transition. In order to quantitatively analyze the impacts, this study proposed a methodology that combines CO2 emissions, energy transition, and water demand. An energy-water integrated assessment model was built, to simulate the future energy and CO2 emissions pathways up to 2050 in China. The water demand of energy systems under both policy scenario (PS) and two mitigation scenarios (2C and 1.5C) are calculated. The key influencing factors of water demand are analysed in two low-water-demand mitigation scenarios (2C-LW and 1.5C-LW). The results showed that China’s future energy system and CO2 emissions pathways change significantly under mitigation scenarios. The timing of the CO2 emissions peak advances from around 2030 under the PS scenario to between 2020 and 2025 in the mitigation scenarios. Near-zero emissions are achieved by 2050 under the 1.5C scenario. However, with no further water-saving measures, water consumption in energy sector would continue to increase under both the policy scenario and mitigation scenarios. This pressure is compounded by certain mitigation technologies, such as inland nuclear power, biomass energy, and CCS technologies. As such, the potential for water conservation in energy system under climate mitigation targets is studied. The results showed that water-saving measures can significantly reduce long-term water demand in the energy system.